A study on the representative point of horse's center of gravity - Li, S.; Dong, Q.; Yu, Y.; Li, L.; Tao, J. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to explore are there bony landmarks on the horse body`s surface matching the motion of center of gravity. The relationship between the bony landmarks and the center of gravity during actual race under Buchner and Kubo horse inertial models were analyzed. Results showed Buchner and Kubo models had high consistency on the kinematic parameters of the center of gravity. Comparing the relationship of the middle of mesoscapula and tail root with the center of gravity in displacement, velocity and the absolute difference, it was found that the middle of mesoscapula under Kubo model is a suitable represent point of the center of gravity among the characteristic points of two models in the motion of observed race horses.